Acute and sub-chronic toxicity of Cajanus cajan leaf extracts - Rong Tang; Ru-hua Tian; Jia-zhong Cai; Jun-hui Wu; Xiao-ling Shen; Ying-jie Hu (Taylor & Francis Group, 2017)
Context: The leaves of Cajanus cajan (L.) Millsp. (Fabaceae) have diverse bioactivities, but little safety data are reported. Objective: This study examines the toxicological profiles of C. cajan leaf extracts. Materials and methods: The leaves were extracted by water or 90% ethanol to obtain water or ethanol extract (WEC or EEC). EEC was suspended in water and successively fractionated into dichloroform and n-butanol extracts (DEC and BEC). Marker compounds of the extracts were monitored by high-performance liquid chromatography (HPLC). Kunming mice were administered with a single maximum acceptable oral dose (15.0 g/kg for WEC, EEC and BEC and 11.3 g/kg for DEC) to determine death rate or maximal tolerated doses (MTDs). In sub-chronic toxicity investigation, Sprague-Dawley rats were orally given WEC or EEC at 1.5, 3.0 or 6.0 g/kg doses for four weeks and observed for two weeks after dosing to determine toxicological symptoms, histopathology, biochemistry and haematology. Results: Flavonoids and stilbenes in the extracts were assayed. In acute toxicity test, no mortality and noted alterations in weight and behavioural abnormality were observed, and the maximum oral doses were estimated as MTDs. In sub-chronic toxicity study, no mortality and significant variances in haematological and biochemical parameters or organ histopathology were observed, but increased kidney weight in 3.0 g/kg WEC- or 3.0 and 6.0 g/kg EEC-treated female rats, and reduced testes and epididymis weight in EEC-treated male rats were recorded. These changes returned to the level of control after recovery period. Conclusion: Acute and sub-chronic toxicity of Cajanus cajan leaf extracts was not observed.